Hubungan Tingkat Kecemasan Ibu Hamil Trimester III dengan Kepatuhan Antenatal Care (ANC) di Masa Pandemi Covid-19 - Rusdiana, Rusdiana; Farantia, Poppy; Mayasari, Dian (Malang Journal of Midwifery (MAJORY), 2023)
The risk of complications from Covid-19 is higher in some susceptible populations, especially pregnant women. The third trimester of pregnancy until the birth process is a period of waiting with full vigilance so that concern about the Covid-19 pandemic situation can affect antenatal care (ANC) adherence of pregnant women during the Covid-19 pandemic. The purpose of this study was to analyze the relationship between the anxiety level of third trimester pregnant women and ANC adherence during the Covid-19 p andemic at the Kartika Jaya Maternity Clinic, Samarinda. This type of research is analytic correlation with a cross-sectional approach, involving 112 respondents in the third trimester of pregnancy using a consecutive sampling technique. The instruments used were the Hamilton Rating Scale for Anxiety (HARS) and ANC compliance questionnaires. Data analysis used the chi square test. The results of the study obtained ? value of 0.003 <? (0.05) meaning that there was a relationship between the anxiety level of third trimester pregnant women and ANC adherence during the Covid-19 period. Compliance of pregnant women with ANC occurs to overcome pregnant women's anxiety about the condition of the womb during Covid-19 because there is awareness of pregnant women in maintaining health, especially during pregnancy. It is hoped that pregnant women will continue to carry out ANC during the Covid-19 period by maintaining health protocols